Inovando o Trabalho de Campo com a Articulação entre Teoria e Prática: as Disciplinas do Curso de Obstetrícia - Silva, Eunice Almeida da; Narchi, Nádia Zanon; Belli, Maria Aparecida de Jesus; Trintinália, Maryam Michelle Jarrouge; Teixeira, Nilva (Revista de Graduação USP, 2017)
This study aims to show the teaching strategy used in the disciplines Administration of Health Care Services and Internship of Administration of Health Care Services, mandatory in the undergraduate course in Obstetrics of the Universidade de São Paulo. The general objective of the strategy was to articulate the content offered in the classroom to the internship practice in management. In 2014, forty-three students attended the subjects, discussed the content in the classroom, carried out visits in the private network services and experienced management practices in health public services. The specific objective of the strategy was to identify and to analyze three problem situations that could hinder the dynamic management of health public services. From the analysis and based on the visits, students in groups drew up a project aimed at improving the management of public services. Projects should answer the question: Is it possible to manage the processes, resources and workers in public health care services in order to add value to them? All answered affirmatively, showing descriptions of how the connections between the concepts discussed in class with the difficulties and possibilities found in the scenarios of the practices were understood.